A nationwide assessment of psychosocial adjustment and its associated factors in people with spinal cord injury and disorders (PA-SCID): the study protocol - Saharuddin, Danial Asyraf; Engkasan, Julia Patrick; Fernandez, Aaron; Chew, Boon How (Universiti Putra Malaysia, 2021)
Introduction: This article aims to describe the study protocol of a nationwide survey on psychosocial adjustment of people with spinal cord injury or disorders (SCID) and its associated factors. SCID is a complex clinical condition and debilitating public health issues to families and societies. Psychosocial adjustment is represented in this study as health-related quality of life, perceived social support, coping, independence, and spiritual well-being. This study aims to determine the psychosocial adjustment of people with SCID in Malaysia. Methods: This is a study protocol for a nationwide cross-sectional postal and online survey of people with SCID. Cross-cultural adaptation and hypothesis-validity testing will be conducted for independence and spiritual well-being measures. A total of 786 eligible participants will be recruited from eight public hospitals in the Peninsular, Sabah, and Sarawak. The questionnaires include the World Health Organization Quality of Life-Brief (WHOQOL-BREF), Spinal Cord Independence Measure – Self-report (SCIM-SR), Brief Coping Orientation to Problems Experienced (Brief COPE), Medical Outcome Survey – Social Support (MOS-SSS) and Functional Assessment of Chronic Illness Therapy – Spiritual Well-being Short Version (FACIT-Sp-12). HRQoL measured by WHOQOL-BREF is the main primary outcome of this study. Independent association between the sociodemographic and clinical characteristics with the outcome variables will be determined separately using multiple linear regression. Discussion: The findings of the study will be informative regarding the causes of SCID and factors associated with psychosocial adjustment in Malaysia. It will benefit future medical and public health initiatives to improve on the existing rehabilitation programs and social services to people with SCID.